2008
DOI: 10.1086/591437
|View full text |Cite
|
Sign up to set email alerts
|

The Magellanic Zoo: Mid‐InfraredSpitzerSpectroscopy of Evolved Stars and Circumstellar Dust in the Magellanic Clouds

Abstract: We observed a sample of evolved stars in the Large and Small Magellanic Clouds (LMC and SMC) with the Infrared Spectrograph on the Spitzer Space Telescope. Comparing samples from the SMC, LMC, and the Galaxy reveals that the dust production rate depends on metallicity for oxygen-rich stars, but carbon stars with similar pulsation properties produce similar quantities of dust, regardless of their initial metallicity. Other properties of the oxygen-rich stars also depend on metallicity. As the metallicity decrea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
171
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(176 citation statements)
references
References 98 publications
5
171
0
Order By: Relevance
“…The theoretical work of Mattsson et al (2008) and Wachter et al (2008) showed that the mass-loss rates of carbon stars may not be sensitive to metallicity. Numerous recent studies using Spitzer spectra of AGB stars in low-metallicity Local Group galaxies (e.g., Sloan et al 2006;Zijlstra et al 2006;Lagadec et al 2007;Matsuura et al 2007;Sloan et al 2008) seem to support this claim. Similar results were obtained by Groenewegen et al (2007), who found in their modeling of the IRS spectra of 60 carbon stars in the Magellanic Clouds that the trend of mass-loss rates with period of luminosity was comparable to that of Galactic sources.…”
Section: Introductionmentioning
confidence: 91%
“…The theoretical work of Mattsson et al (2008) and Wachter et al (2008) showed that the mass-loss rates of carbon stars may not be sensitive to metallicity. Numerous recent studies using Spitzer spectra of AGB stars in low-metallicity Local Group galaxies (e.g., Sloan et al 2006;Zijlstra et al 2006;Lagadec et al 2007;Matsuura et al 2007;Sloan et al 2008) seem to support this claim. Similar results were obtained by Groenewegen et al (2007), who found in their modeling of the IRS spectra of 60 carbon stars in the Magellanic Clouds that the trend of mass-loss rates with period of luminosity was comparable to that of Galactic sources.…”
Section: Introductionmentioning
confidence: 91%
“…The lack of a UV bump could also be caused by efficient grain destruction Sloan et al 2008) favoured by lower dust column densities and harder radiation fields due to the low metallicity. If carbonaceous carriers of the UV bump are more sensitive to harsh environments than silicate ones, then the UV bump strength may be lower in carbon-dust dominated low-metallicity environments than in high-metallicity galaxies, where the dominant population of silicates may also act as carriers of the UV bump.…”
Section: The Carriers Of the Uv Bump And Other Small-size Dust Componmentioning
confidence: 99%
“…The mass-loss efficiency in O-rich stars depends more on metallicity than in C-rich stars, because O-rich dust depends on metallicity-limited elements (Si, Al), while amorphous carbon depends on self-produced C (e.g., Sloan et al 2008Sloan et al , 2012.…”
Section: Mass-loss Ratesmentioning
confidence: 99%